Effects of haptoglobin polymorphisms and deficiency on susceptibility to inflammatory bowel disease and on severity of murine colitis. Issue 4 (27th June 2011) - Márquez, L; Shen, C; Cleynen, I; De Hertogh, G; Van Steen, K; Machiels, K; Perrier, C; Ballet, V; Organe, S; Ferrante, M; Henckaerts, L; Galicia, G; et al.
Abstract : Background: Haptoglobin (Hp) is a haemoglobin-binding protein with immunomodulatory properties. Its gene (16q22) harbours a common polymorphism with two different alleles: Hp1 and Hp2 . Genotype Hp22 has been shown to be over-represented in different immune diseases. Results in Crohn's disease (CD) are contradictory. Aims: To determine whether Hp plays a role in inflammatory bowel disease, both genetically and functionally. Methods: 1061 patients with CD, 755 with ulcerative colitis (UC) and 152 with primary sclerosing cholangitis, as well as 452 healthy controls, were genotyped using touch-down PCR. To confirm association results, 464 CD trios and 151 UC trios were genotyped. Serum Hp concentrations were determined in 62 individuals of different genotype. Colitis was induced in mice with dextran sulphate sodium (DSS) and oxazolone (Oxa). Cytokine production was evaluated by mRNA quantification in colonic tissue and ELISA on supernatants of mesenteric lymph node cells. Results: Prevalence of Hp2 was higher in CD and UC than in controls. In the confirmatory cohorts, Hp2 was over-transmitted to the affected offspring. Serum Hp concentrations were higher in individuals with genotypes Hp11 and Hp21 than in those with Hp22 (1.38 vs 0.89 g/l). DSS- and Oxa-induced colitis were more severe in Hp-deficient mice than in control mice and accompanied by higher concentrations (although not statistically significantly different) of tissue mRNA for cytokines. Interleukin-17 production was significantly higher in the presence of Hp-deficient serum compared with wild-type serum. Conclusions: The Hp gene may play a role in susceptibility to inflammatory bowel disease. Its implication in other immune diseases underscores the common pathways between these diseases. Experimental models of colitis showed that Hp has a protective role in inflammatory colitis, most likely by inhibiting the production of Th1 and Th17 cytokines.